Pengukuran Quality of Service (QoS) Pada Aplikasi File Sharing dengan Metode Client Server Berbasis Android - Doni Priadi (Jurnal Jaringan Telekomunikasi, 2018)
In this research, an application is made that can make it easier to transfer files or data by utilizing a wifi connection on a network and then transferring files via a web browser using Hypertext Transfer Protocol (HTTP) server technology which will be installed on an Android-based smartphone. After that, it is necessary to measure network performance to determine the quality of the network in accessing the application. The measured performance is Quality of Service (QoS), which is a parameter that shows the quality of data packets on the network. Based on the results of measurements carried out by connecting the server to the AH building network and the client accessing from the AI ??building network at the State Polytechnic of Malang, when compared to the ITU-T standard, the application delay is in the very good category, jitter is in the bad category, the throughput value depends on the size. data sent. For packet loss, it is in the very good category. Meanwhile, based on measurements made using the Apache benchmark software, out of the 1000 requests that were tested, none of them failed or failed.